Nano-materials Enabled Thermoelectricity from Window Glasses - Inayat, Salman B. (Nature Publishing Group, 2012)
With a projection of nearly doubling up the world population by 2050, we need wide variety of renewable and clean energy sources to meet the increased energy demand. Solar energy is considered as the leading promising alternate energy source with the pertinent challenge of off sunshine period and uneven worldwide distribution of usable sun light. Although thermoelectricity is considered as a reasonable renewable energy from wasted heat, its mass scale usage is yet to be developed. Here we show, large scale integration of nano-manufactured pellets of thermoelectric nano-materials, embedded into window glasses to generate thermoelectricity using the temperature difference between hot outside and cool inside. For the first time, this work offers an opportunity to potentially generate 304 watts of usable power from 9 m(2) window at a 20°C temperature gradient. If a natural temperature gradient exists, this can serve as a sustainable energy source for green building technology.